Preparation and Characterization of Hydroxyapatite and Optimizing Its Properties Using Regression Model. Issue 1 (August 2021) - Al-Dujaili; Ahmed, Mohammed A.; Aswad; Abbas, Mohsin; Oribi; Ibrahim, Mariam
Abstract: This study clarified the importance of hydroxyapatite in the biological and medical field as alternatives for damaged parts of the bones and teeth. The aim of this study is to preparing the hydroxyapatite from a biological source, bovine femur bones, for its efficiency and low cost. The bovine bone has been converted to hydroxyapatite by a heat treatment method at 1000 °C for 3 hrs. The resulting powder was characterized by X-ray diffraction, Fourier transform infrared spectroscope and particle size. The regression models used for the optimization mechanical and physical properties, by taking density as an independent variable, porosity, hardness and compressive strength as dependent variables. Through regression analysis, it was found that the value of the correlation coefficient (R) is (0.990), while the value of (F) in the ANOVA test was (15.97). In addition to the T-test, which indicates the presence of statistical differences between the variables.